2023
DOI: 10.21203/rs.3.rs-2589328/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinetic modeling and optimization of n-heptane catalytic isomerization using Box-Behnken experimental design

Abstract: The statistical analysis using response surface methodology approach was conducted for optimization of the kinetic conditions of the n-heptane isomerization reaction over Pt-HZSM-5/HMS catalysts. The conditions of the kinetic experiments were as H2 flow rate of 20-45 cc min−1, n-C7 flow rate of 2-4.5 cc h−1, the reaction temperatures in the range of 200-350 °C, and the weight percent of HZSM-5 of 10-40. The results show that the amounts of HZSM-5 into Pt-HMS structure helps the rate of n-heptane isomerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The outcome also suggested that the quadratic model is considered the most suitable for forecasting the response. for determining the optimal level of each variable to achieve maximum adsorption value [31,34,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome also suggested that the quadratic model is considered the most suitable for forecasting the response. for determining the optimal level of each variable to achieve maximum adsorption value [31,34,49].…”
Section: Discussionmentioning
confidence: 99%
“…In the given equation, Y represents the expected response, β0 represents the constant coefficient, βi represents the linear coefficient, βii represents the quadratic coefficient, βij represents the interaction coefficients, and ε represents the error of the model [34][35][36].…”
Section: Experimental Design By Rsmmentioning
confidence: 99%